1983
DOI: 10.1007/bf01531565
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of autistic children: a selective review of available instruments

Abstract: This review examines five measures specifically designed to assess autistic symptomatology: Rimland's Diagnostic Checklist for Behavior-Disturbed Children, the Behavior Rating Instrument for Autistic and Atypical Children, the Behavior Observation Scale for Autism, the Childhood Autism Rating Scale, and the Autism Behavior Checklist. Available studies of reliability and validity issues are discussed. Reliability indices for all scales, except Rimland's Diagnostic Checklist, are at acceptable levels. Each scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…This heterogeneity has been attributed to the structure of the diagnostic systems (Parks, 1983), and to the incorrect use of diagnostic systems (Cohen, Paul, & Volkmar, 1986;Meehl, 1986). Identifying more homogeneous behavioral subgroups would increase the inferential power of developmental, genetic, imaging, neuroanatomic, and neurophysiological studies of autism (Dahl, Cohen, & Provence, 1986;Eaves, Ho, & Eaves, 1994;Horowitz & Rumsey, 1994;Piven & Folstein, 1994;Rapin, 1991;Reichler & Lee, 1987;Tsai & Ghaziuddin, 1992;Waterhouse, 1994).…”
mentioning
confidence: 97%
“…This heterogeneity has been attributed to the structure of the diagnostic systems (Parks, 1983), and to the incorrect use of diagnostic systems (Cohen, Paul, & Volkmar, 1986;Meehl, 1986). Identifying more homogeneous behavioral subgroups would increase the inferential power of developmental, genetic, imaging, neuroanatomic, and neurophysiological studies of autism (Dahl, Cohen, & Provence, 1986;Eaves, Ho, & Eaves, 1994;Horowitz & Rumsey, 1994;Piven & Folstein, 1994;Rapin, 1991;Reichler & Lee, 1987;Tsai & Ghaziuddin, 1992;Waterhouse, 1994).…”
mentioning
confidence: 97%
“…Seldom have the same adaptive behavior measures or screening instruments been applied broadly across a large population cohort (Freeman, Ritvo, & Schroth, 1984;Freeman & Schroth, 1984;Janicki & Jacobson, 1983;Janicki, Lubin, & Freeman, 1983;Parks, 1983;Wing, 1982).…”
mentioning
confidence: 97%
“…Studies of Fragile X and Cornelia de Lange syndromes have identified such differences although this may not be considered for other syndrome groups. However, the original reliability figures were based on percentage agreement, which does not consider the influence of chance and raters were not blind to clinical diagnosis when discriminative validity was tested (Parks, 1983;Volkmar et al, 1988). Further studies using more stringent measures have indicated that internal consistency is good for total score but poor on subscales.…”
Section: Assessment Of Asd In Individuals With Intellectual Disabilitmentioning
confidence: 99%